Cytotoxicity of Thymoquinone (TQ) from Nigella sativa towards human cervical carcinoma cells (HeLa). - Saiful Yazan, Latifah; Ng, Wei Keat; Al-Naqeeb, Ghanya; Ismail, Maznah (Elsevier, 2009)
Thymoquinone (TQ), the bioactive constituent of the volatile oil of Nigella sativa, has been shown to exert anti inflammatory, anti-oxidant and anti-neoplastic effects both in vitro and in vivo. In this study, the cytotoxicity of TQ was evaluated on human cervical carcinoma cells (HeLa). Results showed that TQ exhibited cytotoxic and anti-proliferative activities towards the cells with IC50 value of 2.80±0.10mg/ml and 5.37±0.12mg/ml after 72 hours incubation time as being detected by trypan blue dye exclusion test and MTT assay, respectively. Significant decrease in the percentage of cell viability was observed after the treatment with 1.0, 3.0, 10 and 30mg/ml (p<0.05) indicating that TQ induced cytotoxicity in a dose-dependent manner. IC50 values determined by the trypan blue dye exclusion test were significantly decreased from 5.93±0.81mg/ml (24 hours) to 2.80±0.10mg/ml (72 hours) suggesting that TQ induced cytotoxicity in a time-dependent manner. HeLa cells treated with TQ for 72 hours showed a significant decrease in cell population at G0/G1 phase and significant increase of cell population at sub-G1 phase at 6.0, 10 and 30mg/ml (p<0.05), suggesting that TQ inhibited cell proliferation by induction of apoptosis in the cells. Expression of p53 detected by using the Human p53 ELISA showed that HeLa cells incubated with 10mg/ml of TQ for 72 hours resulted in significant up-regulation of the expression of the protein (p<0.05) compared to the control untreated sample. It is concluded that TQ was cytotoxic towards HeLa cells in a dose- and time-dependent manner and induced apoptosis via p53-dependent pathway.